2019
DOI: 10.1002/jnr.24539
|View full text |Cite
|
Sign up to set email alerts
|

Development of barium‐based low viscosity contrast agents for micro CT vascular casting: Application to 3D visualization of the adult mouse cerebrovasculature

Abstract: Recent advances in three-dimensional (3D) fluorescence microscopy offer the ability to image the entire vascular network in entire organs, or even whole animals.However, these imaging modalities rely on either endogenous fluorescent reporters or involved immunohistochemistry protocols, as well as optical clearing of the tissue and refractive index matching. Conversely, X-ray-based 3D imaging modalities, such as micro CT, can image non-transparent samples, at high resolution, without requiring complicated or ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…To visualize the intact spinal structures, including the vascular, bone, and cartilage tissues, MICROFIL® contrast agent was used to enhance the attenuation of the contrast of the vessels. The viscosity of the contrast agent results in insufficient vascular perfusion, which is another factor that limits the depiction of the intramedullary microvasculature of the spinal cord within the spine vertebral bony column (Hong et al, 2020). Our study also indicated that proper specimen fixation is important in the visualization of the anatomic features of spinal motion segments through SRμCT, including soft tissue and hard tissue that can be simultaneously visualized (Barbone et al, 2021; Jiang et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…To visualize the intact spinal structures, including the vascular, bone, and cartilage tissues, MICROFIL® contrast agent was used to enhance the attenuation of the contrast of the vessels. The viscosity of the contrast agent results in insufficient vascular perfusion, which is another factor that limits the depiction of the intramedullary microvasculature of the spinal cord within the spine vertebral bony column (Hong et al, 2020). Our study also indicated that proper specimen fixation is important in the visualization of the anatomic features of spinal motion segments through SRμCT, including soft tissue and hard tissue that can be simultaneously visualized (Barbone et al, 2021; Jiang et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it minimizes sample dehydration/ shrinkage and corresponding imaging artifacts during the long-lasting high-resolution microCT scans. On the contrary, outside the brain cage, the brains are very susceptible to dehydration, which results in sample shrinkage and imaging artifacts, which are evident especially in the higher magnifications as a feathering (or shadowing) of the images (Hong et al 2020). To mitigate this problem, the researchers often use wet paper tissue or wrap the samples with cling film.…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate this problem, the researchers often use wet paper tissue or wrap the samples with cling film. This reduces the dehydration, but wrapping and unwrapping of the exposed brain often damage the surface vessels (Hong et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of these contrast agents has been applied to the brain either by perfusion or immersion, allowing for cerebrovascular or cellular visualization in micro-CT 30 . The vasculature can be studied using polymerising compounds or agents that penetrate the vessels lumen 3133 3436 , meanwhile, neuronal tissue contrast can be achieved through immersion of the whole brain Different contrasts can be achieved because of the different binding affinities of the stains to the different brain cells 23 . The staining of soft tissues with ionic contrast agents has been used for imaging in the micro-CT of brain 37 and whole-body 38 of zebrafish, as well as, rodent embryos, brains and other organs 28, 29, 38 .…”
Section: Introductionmentioning
confidence: 99%